Analisis pelaksanaan konsep hisbah dalam pentadbiran audit syariah di Bank Islam Malaysia Berhad / Sanusi Abdul Manaf - Sanusi , Abdul Manaf (2017)
Shariah audit administration of Islamic Financial Institutions (IFIs) face several challenges when addressing various issues related to the implementation of Shariah compliance. Key issues include auditor qualifications, Shariah compliance in the development and promotion of products and services, and policies for addressing the issue of Shariah non-compliance. Addressing these issues requires consideration of the concept of Íisbah in the history of Islamic administration. In relation to this, the primary purpose of this study is an examination of theories of Íisbah found in both classical and modern references. Additionally, the study aims to compare elements of contemporary Shariah audit practices in such contexts as the Shariah Governance Framework for Financial Institutions (SGF) to determine similarities and differences among such frameworks to assist in the proposed consolidation of Shariah audit administration in IFIs. The importance of this study is in helping strengthen elements of Íisbah to act as a value-added feature of Shariah administrative audit systems in Malaysia. A qualitative methodology was adopted for this qualitative field study. To obtain information and data, the author examined a number of classic and modern works, as well as examining documentation and conducting interviews. Data from these three methods were analysed to accurately address the research questions. The study found that within the concept of Íisbah, elements of muÍtasib, muÍtasab fih, muÍtasab alaih and nafs al-iÍtisab are considered in the audit system of Bank Islam Malaysia Berhad (BIMB) and the SGF framework. It is hoped that the presence of elements of Íisbah will lead BIMB to seriously promote a Sharia administrative audit system which correctly carries out the functions of Íisbah elements in the context of the Íisbah concept.